2021
DOI: 10.1039/d1qo00365h
|View full text |Cite
|
Sign up to set email alerts
|

Radical 1,2-addition of bromoarenes to alkynes via dual photoredox and nickel catalysis

Abstract: A regioselective, intermolecular 1,2-addition of aryl bromides to alkynes enabled by photocatalytic generation of bromine radicals via photoredox and nickel catalysis is reported. This mild and redox-neutral protocol tolerates a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…With the complexes in hand, control experiments to test the viability of Ni II adducts of 4-bromobenzotrifluoride (complex 73 ), bromobenzene (complex 74 ), and 3-bromotoluene (complex 75 ), which are electronically differentiated, were then carried out (Scheme A–C). , In contrast to previous studies, , bromobenzene and 3-bromotoluene were chosen instead of 2-bromotoluene to avoid the potential for either steric bias or influence of the latter. When complex 73 was used as a catalyst (6 mol %) to promote the coupling of 1 and 4-bromobenzotrifluoride, the decarboxylative arylated product 50a was obtained in 80% yield.…”
Section: Resultsmentioning
confidence: 99%
“…With the complexes in hand, control experiments to test the viability of Ni II adducts of 4-bromobenzotrifluoride (complex 73 ), bromobenzene (complex 74 ), and 3-bromotoluene (complex 75 ), which are electronically differentiated, were then carried out (Scheme A–C). , In contrast to previous studies, , bromobenzene and 3-bromotoluene were chosen instead of 2-bromotoluene to avoid the potential for either steric bias or influence of the latter. When complex 73 was used as a catalyst (6 mol %) to promote the coupling of 1 and 4-bromobenzotrifluoride, the decarboxylative arylated product 50a was obtained in 80% yield.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 5 was obtained from the Heck reaction of 2 a with styrene in moderate yield with 94 % ee [18b] . Moreover, alkenyl borides 6 was obtained from the boronization of 2 a with 67 % yield in 95 % ee [18c] . Likewise, 7 was obtained in 94 % ee from the reduction of the alkenyl chloride [18d] .…”
Section: Resultsmentioning
confidence: 99%
“…To test the possibility of such a dual catalytic carbohalogenation reaction, we chose terminal alkyne 1 and bromostyrene 2 ( E/Z =8:1) as the template substrates (Table 1). We found that irradiation of reaction mixture of 1 and 2 with a 90 W Blue LED in the presence of catalytic Ir[dF(CF 3 )ppy] 2 (dtbbpy)PF 6 , NiBr 2 ⋅ DME, 4,4’‐di‐ tert ‐butyl‐2,2’‐bipyridine L1 (dtbbpy), and diisopropylamine (DIPA) afforded the desired bromo‐1,3‐dienes 3 and 4 in 19% and 21% yield, respectively (entry 1) [13c] . To improve the poor regioselectivity, which, we reasoned, could be deterred by migratory insertion step of alkynes into alkenylnickel species, [15] we further evaluated a series of ligands ( L1 – L6 ) and found that the use of bisoxazoline (BOX) ligands ( L5 – L6 ) led to higher regioselectivity, furnishing the formation of bromo‐1,3‐diene 3 as a single regioisomer with moderate yields (entries 2–6).…”
Section: Methodsmentioning
confidence: 99%